Determinación de la ganancia de pesos en conejos en la etapa de engorde en hembras y machos en el ceypsa - Murillo Bustillos, Jenny Valeria (2016)
The ongoing project was carried out in the Unit of Natural Resources and Agricultural Sciences from the University of Cotopaxi. Its objective was the identification; grouping, tabulation; management and standardization of rabbit-breeding registers to determine both weight gain and selection of outstanding specimens at a certain place over the course of the investigation, on account of resources, installations, and stay for animals, material, and equipment were officially given and covered by the executing institution. 10 rabbits were used. 6 males and 4 females. This was the first group with which the work started. Some were from 9 to 11 weeks old. Sexing of each was done before being put earrings for easy identification. Then, a new group was included at week 5. There were 2 nine-week female rabbits which were introduced to the weight gain stage.